STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALISME GURU DI MI BAHRUL ULUM BUMIAJI KOTA BATU - Maulidia Sukma Febrianti; Anwar Sa’dullah; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Becoming a professional teacher requires the support of the principal. The principal of the madrasa has a strategy to improve teacher professionalism. This study discusses the strategy of madrasah principals in improving teacher professionalism at MI Bahrul Ulum Bumiaji. This research was conducted at MI Bahrul Ulum Bumiaji. This research is motivated by the importance of professionalism for teachers. The purpose of this study was to determine the strategy of madrasah principals in improving teacher professionalism at MI Bahrul Ulum Bumiaji Batu City. This research uses a qualitative approach and type of case study research. Data collection techniques in this study were observation, interviews, and documentation. The professionalism of teachers at MI Bahrul Ulum Bumiaji is being able to master pedagogic competence and professional competence. The teacher is able to manage the class and understand the character of the students. The role of the principal in improving teacher professionalism is as an administrator, supervisor, leader, and motivator. In improving the professionalism of teachers at MI Bahrul Ulum Bumiaji, of course, there are supporting and inhibiting factors that can affect the increase in teacher professionalism.